2020
DOI: 10.1093/jtm/taaa095
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in effective reproduction number of COVID-19 is higher in countries employing active case detection with prompt isolation

Abstract: Highlight Countries that implemented liberal testing with active case finding and prompt isolation, combined with contact tracing and quarantine, were more successful in reducing the reproduction number compared to countries that primarily relied on social distancing and lockdown measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 5 publications
3
42
0
Order By: Relevance
“…These suggest that effective test, isolate, and trace approaches were able to control the epidemic with moderate levels of physical distancing. 27 This finding corroborates the experience of other countries. In Hong Kong, case isolation and contact tracing were combined with other physical distancing measures (but no lockdown), which resulted in an estimated effective reproduction number near 1 for 8 weeks.…”
Section: Discussionsupporting
confidence: 87%
“…These suggest that effective test, isolate, and trace approaches were able to control the epidemic with moderate levels of physical distancing. 27 This finding corroborates the experience of other countries. In Hong Kong, case isolation and contact tracing were combined with other physical distancing measures (but no lockdown), which resulted in an estimated effective reproduction number near 1 for 8 weeks.…”
Section: Discussionsupporting
confidence: 87%
“…Coronavirus disease 2019 (COVID‐19) is an acute respiratory infectious disease caused by severe and highly contagious acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2; the Coronaviridae family). Although previous studies suggested that the basic reproduction number (R0) of SARS‐CoV‐2 was between 2 and 3, the countries with prompt isolation were successful in reducing the reproduction number 1 . Extensive research has shown that the total mortality rate is 5.6%, lower than SARS (13%) and MERS (35%) 2 .…”
Section: Introductionmentioning
confidence: 97%
“…No approved com mercial tests were available when the pandemic emerged, so the gov ernment has decided "to provide first-generation in-house assays for public health laboratories as an interim measure and for gradual migration to a commercial alternative." 3 We urge the government to reconsider this commitment to unspecified commercial contracts that cannot supply the 10 million tests per day needed for weekly testing in the UK. Rapid tests administered by a trained person, although essential in airports and various other public venues, are not suitable for weekly whole-population screening.…”
Section: Unnecessary Obstacles To Covid-19 Mass Testingmentioning
confidence: 99%
“…These countries employed isolation of all cases, even mild ones, often using isolation shelters, hospitals, or other institutions such as hotels. 3,4 Careful study of the sequential mounting of public health responses in Wuhan, China, to combat their explosive outbreak in January and February, 2020, showed five distinct phases. Only in the fourth and fifth phases, when isolation shelters for all cases (even mild cases) were instituted, did the epidemic curve not only flatten but show a rapid decline in daily new cases, down to zero within a matter of weeks.…”
mentioning
confidence: 99%